2014
DOI: 10.1007/s10661-014-4134-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug-resistant, coagulase-positive Staphylococcus aureus in nasal carriage, food, wastewater and paper currency in Jalandhar city (north-western), an Indian state of Punjab

Abstract: Development of multidrug-resistant pattern in the bacterial community is a major threat to the society. Staphylococcus aureus is perhaps the pathogen of the greatest concern because of its inherent virulence, its ability to cause a diverse array of life-threatening situations and capacity to adapt to different environmental conditions. The aims of this study is to investigate the multidrug-resistant pattern of the coagulase-positive S. aureus isolated from nasal carriage, food, paper currency and wastewater sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…In this study, the occurrence of S. aureus nasal carriage of healthy 3-6-year-old children in Hungary was found to be 21.3%, which correlates well with international data [3,15]. A cross-sectional study published in 2013 compared the prevalence of nasal S. aureus carriage of healthy patients in nine European countries (involving >32,000 people), including Hungary [16].…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the occurrence of S. aureus nasal carriage of healthy 3-6-year-old children in Hungary was found to be 21.3%, which correlates well with international data [3,15]. A cross-sectional study published in 2013 compared the prevalence of nasal S. aureus carriage of healthy patients in nine European countries (involving >32,000 people), including Hungary [16].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the transmission of pathogenic species, such as Escherichia coli or S. aureus , from banknotes to humans has been observed (Gedik et al, 2013). Additionally, bacteria with antibiotic resistance on currency notes have been reported around the world (Gabriel et al, 2013; Akoachere et al, 2014; Kumar et al, 2015). It was suggested that “banknotes could serve as a vehicle for transmission of drug resistant pathogenic” (Akoachere et al, 2014; Angelakis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The source of S. aureus could be from the slaughterhouse, livestock and the food handlers. The presence of S. aureus is inevitable as S. aureus can be found in animals especially in the skin, mucous membrane of the upper respiratory tract, lower urogenital tract and digestive tract (Kluytmans, 2010;Kumar et al, 2015). Additionally, a wide range of animals and birds carries S. aureus (Food Standard Agency, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, the drugs are still ongoing clinical trials. In addition, Kumar et al (2015) suggested the need for organizing health and hygienerelated programs to the public as to raise the awareness related to S. aureus which emphasizes on sanitary and drug-related guidelines.…”
Section: Resultsmentioning
confidence: 99%